The role of S100A8 and S100A9 in external auditory canal cholesteatoma - He, Guanwen; Han, Weijing; Zhu, Zhongshou; Wei, Rifu; Lin, Chang (Frontiers in Immunology, 2024)
Background Studies indicated that diverse cellular mechanisms including epithelial migration and hyper-proliferation, inflammatory responses, and enzymatic bone erosion were involved in the pathogenesis of cholesteatoma. S100A8 and S100A9, which are Ca2+-binding proteins belonging to the S100 family, can trigger the signaling pathways involved in the inflammatory processes, and a variety of cellular processes includes cell cycle progression, proliferation, and cell migration. However, the role of S100A8 and S100A9 and their associated inflammation and other signaling pathways in cholesteatoma have not been investigated yet. This study aimed to investigate the role of S100A8 and S100A9 in external auditory canal cholesteatoma and their potential pathological mechanisms. Methods The study conducted histological staining, immunostaining, PCR, and Western blot to investigate the expression of S100A8/A9 and its related pathways in clinic EACC and the murine model of EACC. Results Our data showed that there were increased mRNA and protein levels of S100A8 and S100A9 in clinical and animal models of EACC and the S100A8/A9 heterodimer protein was increased in the EACC model. Our study further demonstrated that the increased S100A8 and S100A9 were associated with apoptosis as well as inflammatory (TGF-β, IFN-γ, and IL-10) and angiogenetic (VEGF, HGF/SF, and c-Met) molecular pathways. The correlation analysis indicated that S100A8 and S100A9 were correlated with clinic staging, apoptosis, and inflammatory and angiogenetic factors. Conclusion This study provided novel insight into the role of S100A8 and S100A9 associated with pathological mechanisms of EACC.